Feasibility test of a concurrent process for CO2 reduction and plastic upcycling based on CO2 plasma jet. Issue 52 (October 2021) - Kang, Hongjae; Kim, You-Na; Song, Hohyun; Lee, Heesoo; Kim, Kwan-Tae; Song, Young-Hoon; Lee, Dae Hoon; Li, Oi Lun
Highlights: Concurrent process for CO2 reduction and plastic upcycling by CO2 plasma. Chemical upcycling of low-density polyethylene to C1 and C2 gases. Syngas to CO2 ratio was achieved up to 32 % in batch scale reactor. Promising approach for an efficient and scalable CO2 utilization. Abstract: A novel concurrent process for CO2 reduction and plastic upcycling was successfully developed based on a rotating gliding arc plasma process, where CO2 gas and Low-density polyethylene (LDPE) powder were used as reactants for the process. Herein, the LDPE powder was regarded as an alternative of plastic waste, and the high temperature of the plasma jet thermochemically decomposed the plastic powder. Based on gas chromatography analyses, the yields of the C1 and C2 chemicals were confirmed, which demonstrated the possibility for the chemical upcycling of the plastic powder with CO2 plasma jet. At the same time, the conversion of CO2 at the exhaust gas increased with increasing electric power of the plasma jet. In addition, as the electric power further enhanced, the reverse reactions were efficiently suppressed by the chemical quenching process due to complete depletion of the oxygen by the light hydrocarbon gases generated from the pyrolysis of the plastic powder. Based on the molecular balance of C and O, the calculated syngas to CO2 ratio was achieved up to 32 % in a batch-type plasma reactor with a power supply of 1170 W. It is rational inference that the efficiency will be significantly improved if a plug-in type plasma reactor with higher power supply is implemented. In conclusion, this novel concurrent process would be a promising approach for an efficient and scalable technology of CO2 utilization.